54.6k views
1 vote
simplify the expression write the result using positive exponents only assume that all bases are not equal to zero

simplify the expression write the result using positive exponents only assume that-example-1
User Dispix
by
5.4k points

1 Answer

5 votes

Consider the formulae,


\begin{gathered} (ab)/(cd)=(a)/(c)*(b)/(d) \\ (x^a)/(x^b)=x^(a-b) \end{gathered}

Now, solve the given expression as follows,


\begin{gathered} (-12m^4)/(-3m^3) \\ =(-12)/(-3)*(m^4)/(m^3) \\ =4* m^(4-3) \\ =4* m^1 \\ =4m \end{gathered}

Thus, the simplification yields '4m'.

User Redplane
by
5.2k points